Respuesta :

snog

Answer:

[tex]y^{-5}[/tex]

Step-by-step explanation:

The Exponent Quotient Rule states that if two terms of the same base are being divided by each other, then the simplified expression is the base to the first power subtracted by the second power. As an algebraic equation, that would be [tex]\frac{x^{a} }{x^{b} } =x^{a-b[/tex], where [tex]x[/tex] is the common base and [tex]a[/tex] and [tex]b[/tex] are the exponents.

In this case, [tex]x=y[/tex], [tex]a=2[/tex], and [tex]b=7[/tex], so we know that [tex]\frac{y^{2} }{y^{7} } =y^{2-7}=y^{-5}[/tex]. Hope this helps!